2022
DOI: 10.54941/ahfe1001871
|View full text |Cite
|
Sign up to set email alerts
|

Design of a devices’ system with tangible interface aimed to an inclusive smart working experience and wellbeing

Abstract: In Europe, the demographic profile is towards an increasingly aged workforce [1], characterized by a significant aging of the population. The people aged 55 years or more accounted for one fifth of the total workforce, and as one consequence of increasing longevity, must work more years before retirement [2].Aging of the workforce is a growing problem for many developed and developing countries, pushing companies to explore ways to keep older workers employed for a longer period of time and to support them to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Among the searched and recent literature, it was obviously found by Bella et al in 2022 in an integrative review that aimed to summarize conceptual models of nurses’ organizational well-being and identify common variables among them, and they concluded that there is no consensus in the nursing literature on an all-encompassing conceptual model of nurses’ organizational well-being or on working environment characteristics to be studied or monitored for defining nurses’ well-being; which it was implied that reaching to a consensus on the definition of nurses’ organizational well-being model and its variables could facilitate nursing management in monitoring and intervening on nurses’ work-life quality and in improving nursing performance and caring outcomes. 35 …”
Section: Introductionmentioning
confidence: 99%
“…Among the searched and recent literature, it was obviously found by Bella et al in 2022 in an integrative review that aimed to summarize conceptual models of nurses’ organizational well-being and identify common variables among them, and they concluded that there is no consensus in the nursing literature on an all-encompassing conceptual model of nurses’ organizational well-being or on working environment characteristics to be studied or monitored for defining nurses’ well-being; which it was implied that reaching to a consensus on the definition of nurses’ organizational well-being model and its variables could facilitate nursing management in monitoring and intervening on nurses’ work-life quality and in improving nursing performance and caring outcomes. 35 …”
Section: Introductionmentioning
confidence: 99%